Education Expression of Multiperspective Approach on History Curriculum of Basic and Secondary Education - Bitautas, Algis (Pedagogika, 2015)
In the article education expression of multiperspective approach on history curriculum of basic and secondary education is thoroughly analyzed (1990–2011 y.). According to the work of contemporary foreign specialists of history didactics, the author presents the history conception of multi – perspective view in teaching and learning. The author carried out the analysis of curriculum seeking to distinguish the essential content change of curriculum structure and the teaching and learning of history in the period of twenty years of independence.